The New Boardroom Leaders : How Today's Corporate Boards Are Taking Charge. - Ward, Ralph D. (ABC-CLIO, 2008)
For generations, the cozy, standard model of boardroom leadership was simple: The CEO was also Chairman of the Board, and directors rubberstamped his initiatives. The 2002 Sarbanes-Oxley Act forced radical change on all U.S. public corporations: The board must now hold sessions without management, key committees have tough new independence rules, and all board members now face an unavoidable legal responsibility to provide truly independent oversight of the corporation. Missteps can put companies and individual directors in serious legal danger. The result is an urgent demand that corporate bo.